Proceedings of the International Conference on the Development of Education in Eurasia (ICDEE 2019) 2019
DOI: 10.2991/icdee-19.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the Environment of Professional Self-Determination in Russian Schools

Abstract: Global changes occurring in all walks of life have also had an impact on education. The school must prepare a graduate who is able to successfully socialize and be in demand and competitive. That is why, the problem of professional self-determination and the choice of future profession by students is particularly acute. The training of professionals of the 21st century should be carried out in educational organizations with prevocational training, which is the basis for obtaining high-quality professional educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Es en las escuelas donde ocurre la formación del personal profesional del siglo XXI. Esta formación debe realizarse para obtener una educación profesional de alta calidad y garantizar la competitividad (Afanasyev et al, 2019). El inicio del trabajo depende de contenidos objetivos y subjetivos, hasta la fecha no existe un sistema de orientación vocacional-profesional eficaz (Nemova et al, 2017).…”
Section: Resultados Y Discusión Caracterizaciónunclassified
“…Es en las escuelas donde ocurre la formación del personal profesional del siglo XXI. Esta formación debe realizarse para obtener una educación profesional de alta calidad y garantizar la competitividad (Afanasyev et al, 2019). El inicio del trabajo depende de contenidos objetivos y subjetivos, hasta la fecha no existe un sistema de orientación vocacional-profesional eficaz (Nemova et al, 2017).…”
Section: Resultados Y Discusión Caracterizaciónunclassified
“…With modern technology continuing to develop, it turns out that the skills needed by students in the 21st century are also different from those of previous generations. This is because the form of learning for 21st century students is more self-oriented by utilizing technology to work on projects more efficiently (Afanasyev et al, 2019;Dawood et al, 2021). The use of technology gives students the advantage to explore and create new experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis made by K.S. Burov [3] of multiple studies on the issue also showed that selfdetermination is developed by acquiring attitudes, personal and professional experience after mastering certain norms, values and purposes and is associated with search for meanings. It happens under the influence of inner choice and external factors (parents, friends, conceptions, and etc.).…”
Section: E3smentioning
confidence: 99%